Suppression of Migration and Invasion by 4-Carbomethoxyl-10-Epigyrosanoldie E from the Cultured Soft Coral Sinularia sandensis through the MAPKs Pathway on Oral Cancer Cells - Rou-Yi Fang; Yueh-Wen Liu; Yih-Gang Goan; Jen-Jie Lin; Jui-Hsin Su; Wen-Tung Wu; Yu-Jen Wu (Advances in Pharmacological and Pharmaceutical Sciences)
The primary reason for cancer-related fatalities is metastasis. The compound 4-carbomethoxyl-10-epigyrosanoldie E, derived from the Sinularia sandensis soft coral species grown in cultures, exhibits properties that counteract inflammation. Moreover, it has been observed to trigger both apoptosis and autophagy within cancerous cells. This research focuses on examining the inhibitory impact of 4-carbomethoxyl-10-epigyrosanoldie E on the migration and invasion processes in Cal-27 and Ca9-22 oral cancer cell lines. To assess how this compound affects cell migration and invasion, the Boyden chamber assay was employed. Furthermore, Western blot analysis was utilized to explore the underlying molecular mechanisms. In a dose-dependent manner, 4-carbomethoxyl-10-epigyrosanoldie E notably decreased the levels of matrix metalloproteinase-2 (MMP-2) and MMP-9, along with urokinase-type plasminogen activator (uPA), in both Cal-27 and Ca9-22 cell lines. Conversely, it elevated the concentrations of tissue inhibitors of metalloproteinases-1 (TIMP-1) and TIMP-2. In addition, the treatment with this compound led to the inhibition of phosphorylation in extracellular signal-regulated kinase (ERK), p38, and c-Jun N-terminal kinase (JNK). It also curtailed the expression of several key proteins including focal adhesion kinase (FAK), protein kinase C (PKC), growth factor receptor-bound protein 2 (GRB2), Rac, Ras, Rho A, mitogen-activated protein kinase kinase kinase 3 (MEKK3), and mitogen-activated protein kinase kinase 7 (MKK7). Furthermore, the expression levels of IQ-domain GTPase-activating protein 1 (IQGAP1) and zonula occludens-1 (ZO-1) were significantly reduced by the compound. The ability of 4-carbomethoxyl-10-epigyrosanoldie E to inhibit the migration and invasion of Cal-27 and Ca9-22 oral cancer cells was observed to be dose dependent. This inhibitory effect is primarily attributed to the suppression of MMP-2 and MMP-9 expression, as well as the downregulation of the mitogen-activated protein kinase (MAPK) signaling pathway.